Formulation and Stability Test of Eel Fish (Anguilla marmorata (Q.) GAIMARD) Oil Extract Cream - Jamaluddin; Asriana Sultan; Nurul Fitria (Media Publikasi Cendekia Indonesia, 2022)
Eel fish (Anguilla marmorata (Q.) Gaimard) on Silver eel phase contains unsaturated fatty acids such as omega-3, omega-6, EPA, DHA and vitamin A which is known to overcome various functions of body tissues. The high content of fatty acids will facilitate oxidation, making it difficult for storage and causing rancidity, thus creating a new innovation such as being formulated into cream. This study aims to formulate the silver eel (Anguilla marmorata (Q.) Gaimard.) Oil extracts in the form of cream dosage preparations and evaluates the cream dosage using physical test parameters to maintain the quality of the cream produced. This study used laboratory experimental methods and the cream formulations were made in 4 formulas, they are F0, F1, F2 and F3 with the respective concentrations of stearic acid emulsifier 6%, 8%, 10% and triethanolamine 2%, 2%, and 3.5. %, and F0 as negative controls. The result obtained test showed that the F3 positive control cream preparation met the organoleptic requirements, the result of homogeneity test was homogeneous and there were mo coarse particles, the dispersion of the cream was 6.87 cm (5-7 cm), adhesion of the cream was 4.21 seconds (>4 seconds), cream pH was 6.25 (4.5-6.5). The F3 formula gave a significant value to the characteristics of the cream